Mechanistic insights of adipocyte metabolism in regulating breast cancer progression. (May 2020) - Zhang, Fuchuang; Liu, Suling
Graphical abstract: Abstract: Adipocyte account for the largest component in breast tissue. Dysfunctional adipocyte metabolism, such as metaflammation in metabolically abnormal obese patients, will cause hyperplasia and hypertrophy of its constituent adipocytes. Inflamed adipose tissue is one of the biggest risk factors causing breast cancer. Factors linking adipocyte metabolism to breast cancer include dysfunctional secretion of proinflammatory mediators, proangiogenic factors and estrogens. The accumulation of tumor supporting cells and systemic effects, such as insulin resistance, dyslipidemia and oxidative stress, which are caused by abnormal adipocyte metabolism, further contribute to a more aggressive tumor microenvironment and stimulate breast cancer stem cell to influence the development and progression of breast cancer. Here, in this review, we focus on the adipocyte metabolism in regulating breast cancer progression, and discuss the potential targets which can be used for breast cancer therapy.